Optimalisasi Waktu Dalam Pembangunan Blok P1701/1702 Pada Kapal Cruide Oil Tanker Di PT. Daya Radar Utama Unit Lamongan - Oktavian Perdana Putra; Endang Pudji Purwanti; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
PT Daya Radar Utama is one of the shipyards that has a prominent quality in the design of several shipyards in Indonesia. In meeting the needs of consumers, the company certainly has an estimated duration of project implementation and good human resource planning. That is, the project must be completed before or on the specified time. In estimating work time and productivity, optimization is needed. Optimization analysis of project time is used to find out how long it will take for a project to be completed and to look for the longest possible time in project imple-mentation with the PERT (Project Evaluation and Review Technique) and CPM (Critical Path Method) methods. From the results of the critical path analysis using network planning, it is found that the longest time needed to complete the work for the construction of Block P 1701/1702 on the Cruide Oil Tanker is based on the calculation of the critical path which is 4728.2 minutes, while the average time is optimistic and pessimistic. in the completion of the project for 4723.63 minute. From the normal time the work productivity is calculated to determine the work-load of each activity, namely the initial blasting work at 6707.8 kg / hour, marking plate work at 6030.3 kg / hour, cutting plate work 2072.9 kg / hour, work bending plate of 53783.7 kg / hour, welding T joint (SMAW) work 4942.05 kg / hour, Weld-ing Butt Joint (FC